Ion Anisotropy in Earth's Magnetotail Current Sheet: Multicomponent Ion Population. Issue 5 (31st May 2019) - Artemyev, A. V.; Angelopoulos, V.; Vasko, I. Y.; Zhang, X.‐J.; Runov, A.; Zelenyi, L. M.
Abstract: The configuration and stability of the magnetotail current sheet, which determine the dynamics of the entire magnetosphere, largely depend on the ion kinetics as inferred from the velocity distribution function. This distribution is shaped by various transient acceleration processes and by contributions from the ionosphere and the distant magnetotail. Investigating the ion distribution is thus crucially important for adequate modeling of the current sheet stability. This necessitates spacecraft observations of the ion distribution in a wide energy range, from ionospheric outflow energies (below 1 keV) to high energies (approximately hundreds of kiloelectron volts). Using combined measurements of Electrostatic Analyzer and Solid State Telescope onboard Time History of Events and Macroscale Interactions during Substorms in 2008–2009 tail seasons, we demonstrate that the ion distribution in the quiet magnetotail current sheet (at times devoid of fast plasma flows and large electric fields) consists of three populations: a subthermal field‐aligned anisotropic population (contributing ∼90% to the total density but only ∼20% to the total pressure), an isotropic thermal population (contributing ∼10% of the total density and ∼60% of the total pressure), and a transversely anisotropic suprathermal population (contributing <1% of the total density and ∼20% of the total pressure). The suprathermal population may include high‐energy ions moving along transient (Speiser) orbits. The competing effects of subthermal and suprathermal partial pressure anisotropies result in an almost isotropic total (combined) ion pressure. We characterize the dependence of the ion distribution characteristics, including the anisotropy of different populations on local plasma sheet activity (ion flows and electric fields). We discuss the implications of our results for current sheet modelling. Key Points: Ion distribution in the quiet magnetotail current sheet consists of three populations with different partial pressure anisotropies The thermal ion population is almost isotropic, but subthermal and suprathermal populations are field aligned and transversely anisotropic During intervals with large plasma flows and strong electric fields, the thermal ion population also becomes transversely anisotropic